Antibacterial Activity of Origanumvulgare Leaves against Different Types of Bacteria Isolated from Urinary Tract Infection Patients in Baghdad/Iraq - Hayfaa M. Fahad (Journal of Global Pharma Technology, 2018)
In the gift study, antibacterial drug potency of Origanumvulgare was studied on four sorts of morbific microorganism isolated from urinary tract infection patient samples, Staphylcoccus aureus, E. coli, Klebsiella pneumonia, and Sallmonellatyphi by agar well diffusion assay. The repressive effects of this leaves extract were compared with control distilled water. The inhibition result of Origanumvulgare in numerous concentration against microorganism growth were studied, the results showed that there's an excellent inhibition growth on all studied microorganism isolates except Klebsiella pneumonia. This study conclude that the data ensure the antibacterial drug potential and highlight the promising role of oregano as new lead structure within the explore for novel antibacterial drug agents. Therefore, any experiment involving a bigger sample size and extract a concentration is deserve analysis.Keywords: antibacterial drug, Vulgare.